How and when is academic stress associated with mobile phone addiction? The roles of psychological distress, peer alienation and rumination. - Yanhong Zhang; Miao Han; Shuailei Lian; Xiaoxuan Cao; Lei Yan (PLoS ONE, 2024)
Background Mobile phone addiction has a high detection rate among adolescents and is thought to be related to academic stress. However, the underlying mechanisms in this relation were still unclear. The present study tested the mediating role of psychological distress and the moderating roles of peer alienation and rumination in the relationship between academic stress and mobile phone addiction. Methods A total of 742 middle school students were recruited to complete measures of academic stress, psychological distress, mobile phone addiction, peer alienation, rumination, and demographic variables. Regression-based statistical mediation and moderation were conducted using the PROCESS macro for SPSS. Results The results indicated that academic stress was significantly and positively associated with mobile phone addiction, and this link could be mediated by psychological distress. Moreover, this indirect effect was moderated by both peer alienation and rumination. Specifically, the mediating effect of psychological distress was stronger for adolescents with higher levels of peer alienation or adolescents with higher levels of rumination, as well as those with both higher levels of peer alienation and rumination. Conclusion The findings of this study enrich our understanding of how and for whom academic stress is correlated with mobile phone addiction. Education experts and parents should pay special attention to adolescents suffering from academic stress, especially those with higher peer alienation and rumination, and help them get rid of mobile phone addiction.